2010
DOI: 10.4314/bajopas.v1i1.57513
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <i>Eschericia coli</i> 0157:H7 in fresh and roasted beef in Kano City, Nigeria

Abstract: The prevalence of Enterohemorrhagic Escherichia coli 0157:H7 in 300 fresh beef and 150 roasted beef samples from Kano city Nigeria was determined, by direct plating on Sorbitol MacConkey agar (CT-SMAC) supplemented with Cefexime 50µg/L and Potassium tellurite 25mg/L and resuscitation on Trypticase Soy Broth (TSB) at 25 0 C for two hours for roasted beef samples. Presumptive colonies were confirmed by using E. coli 0157:H7 latex agglutination test kit. Prevalence rate of 53% was obtained in fresh beef and 25.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
0
5
3
Order By: Relevance
“…However, the present finding is higher than some other reports from Ethiopia, such as 1.3% in Addis Ababa [ 25 ], 2.7% in Haramaya University [ 24 ], and 6.7% in Mekele [ 35 ], and also from other countries in the world, such as 3.76% in Botswana [ 36 ], 1% in Ireland, 0.3% in the Czech Republic, and 0.3% in the Netherlands [ 37 ]. On the other hand, other scholars reported much higher results than the present findings: 60% from street meat sellers in Mekele town and 19.8% and 53% in Nigeria [ 38 ]. The overall variations in the prevalence of E. coli O157 : H7 might be due to the difference in sample size, sampling techniques, laboratory methodologies, study areas, time, and hygienic conditions employed [ 26 , 39 ].…”
Section: Discussioncontrasting
confidence: 91%
“…However, the present finding is higher than some other reports from Ethiopia, such as 1.3% in Addis Ababa [ 25 ], 2.7% in Haramaya University [ 24 ], and 6.7% in Mekele [ 35 ], and also from other countries in the world, such as 3.76% in Botswana [ 36 ], 1% in Ireland, 0.3% in the Czech Republic, and 0.3% in the Netherlands [ 37 ]. On the other hand, other scholars reported much higher results than the present findings: 60% from street meat sellers in Mekele town and 19.8% and 53% in Nigeria [ 38 ]. The overall variations in the prevalence of E. coli O157 : H7 might be due to the difference in sample size, sampling techniques, laboratory methodologies, study areas, time, and hygienic conditions employed [ 26 , 39 ].…”
Section: Discussioncontrasting
confidence: 91%
“…The difference in the overall prevalence observed among the three types of meat samples in present study is high (13.3%) in beef, but relatively similar between sheep meat (9.4%) and goat meat (7.8%). In contrast, the prevalence of E. coli O157:H7 in beef in this study was higher than the 8.8% prevalence reported by Abong (2008) in South Africa and Hajian et al (2011) in Iran; and lower than 53% prevalence reported by Dahiru et al (2008) in fresh beef meat in Nigeria.…”
Section: Discussioncontrasting
confidence: 85%
“…The overall prevalence of E. coli O157:H7 from bovine meat in the present study (21.11%) was higher than the 4.2% reported by [18] and 10.2% by [19] in various areas in Ethiopia. In contrast, the results obtained in this study was higher than the 8.8% prevalence reported by [20] in South Africa and [21] in Iran; and lower than 53% prevalence as reported by [22] in fresh beef meat in Nigeria. The presence of E. coli O157: H7 in meat might be due to contamination either from gastrointestinal content and/or skin [23].…”
Section: Discussioncontrasting
confidence: 99%